OVERVIEW OF DEEP GEOLOGICAL CO2 STORAGE AND ITS AREA SELECTION METHOD - Lucas Donny Setijadji (Geological Engineering Department Universitas Gadjah Mada, 2015)
Geological sequestration of CO2 inside deep geologic formations is revolutionary among several other initiatives to combat the global warming. This method is already approved globally as a reliable and likely to be the only option that will allow removing CO2 in large enough quantities over short enough times to make a real difference. The first step of any geological CO2 storage projects is to select appropriate sedimentary basins in which CO2 will be injected and stored temporarily or permanently within permeable geological layers. The criteria for site selection methods are here explained based on summary from stateof-the-art research findings now exist. This method is planned to be applied for a more detailed mapping of potential sedimentary basins in Indonesia and neighboring regions. Keywords: Sequestration, sedimentary basin, geological layers.